DISTRIBUSI DIAMETER TANAMAN SENGON (Paraserianthes falcataria) SEBAGAI INDIKATOR PERTUMBUHAN NORMAL: Sengon Plant Diameter Distribution (Paraserianthes falcataria) as Normal Growth Indicators - Bela Safitri; Wahyudi Wahyudi; Christopheros (HUTAN TROPIKA, 2020)
Sengon (Paraserianthes falcataria (L) Nielsen) is one of some exotic plants, so that it issuitable for planting on mounds of peat-swamp land in support of revegetation andreforestation, and also to develop plantation forest. This plant have the short rotation,high economic and ecologically value. The aims of research was to know the diameterdistribution of sengon to detect normal growth as well as they were planted on themounds of peat-swamp land and on the traditionaly peat swamp land that floodingperiodically. Data were analized using polynomial equations to form the distributiongraphs. Based on result, at the 4.5 years old of sengon planted on the the mounds ofpeat-swamp land and on the traditionaly peat swamp land indicated the normal graph andabnormal graph respectively. Sengon that planted on the mounds of peat swamp landformed the polynomial equation Y= -35,4 + 47,043X – 6,7857 X2 with coefficient ofdetermination (R2) namely 90.41%, meanwhile Sengon that planted on the traditionalypeat swamp land formed the polynomial equation Y= -10 + 53,643X – 17,571 X2+ 1,5X3 with coefficient of determination (R2) namely (R2) namely 85.99%. Therefore,sengon that planted on the mounds of peat swamp land growth better than sengon thatplanted on the traditionaly of peat swamp landKeywords: Growth, polynomial, sengon, peat swamp land